1996
DOI: 10.1111/j.1432-1033.1996.0460u.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expression of a cDNA Clone Encoding Human Kynureninase

Abstract: Kynureninase (L-kynurenine hydrolase), a pyridoxal-5'-phosphate-(pyridoxal-P)-depe11dent enzyme, catalyses the cleavage of L-kynurenine and L-3-hydroxykynurenine into anthranilic and 3-hydroxyanthranilic acids, respectively. In this report, we describe the isolation of a cDNA clone encoding human kynureninase. Degenerate oligonucleotides designed from the amino acid sequences of peptides from rat liver kynureninase, were used as primers for reverse-transcription PCR of rat kidney RNA. The resulting rat cDNA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
30
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
5
30
0
Order By: Relevance
“…Furthermore, inspection of the human kynureninase amino acid sequence showed the existence of a consensus sequence at the pyridoxal phosphate binding site. The recombinant protein major molecular and kinetic properties essentially resembled those already described for the mammalian enzyme (Alberati-Giani et al, 1996b).…”
Section: B Aerobic Pathwaysupporting
confidence: 49%
See 2 more Smart Citations
“…Furthermore, inspection of the human kynureninase amino acid sequence showed the existence of a consensus sequence at the pyridoxal phosphate binding site. The recombinant protein major molecular and kinetic properties essentially resembled those already described for the mammalian enzyme (Alberati-Giani et al, 1996b).…”
Section: B Aerobic Pathwaysupporting
confidence: 49%
“…The most extensive studies on this enzyme have been conducted in rats (Kaway et al, 1988). Kinetic measurements indicate a clear preference of the enzyme for L-3-hydroxykynurenine respect to the other substrate L-kynurenine (Takeuchi et al, 1980;Alberati-Giani et al, 1996b). From rat liver 3-hydroxylkynureninase amino acid sequence, it has been possible to identify the coenzyme pyridoxal phosphate-binding residue, as LYS*'~.…”
Section: B Aerobic Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to IDO and K3H, human kynureninase is significantly activated by bacterial lipopolysaccharides and proinflammatory cytokines in human monocyte-derived macrophages [61]. The human cDNA codes for a protein of 456 residues, with a M r of 52,400 [70,71]. Northern blot analyses performed on different human organs and tissues reveal that the enzyme is ubiquitous, being mostly expressed in the liver, placenta and lung [70].…”
Section: Kynureninasementioning
confidence: 99%
“…In particular, the exogenous administration of 3-HK in adult insects profoundly affects locomotive activity and can culminate in irreversible paralysis and death (15,16). The biochemical description of the kynurenine pathway from a number of vertebrates revealed that 3-HK can undergo two alternative fates: either (i) it is hydrolyzed by a specific kynureninase to alanine and 3-hydroxyanthranilic acid, feeding the de novo synthesis of the essential cofactor NAD (17), or (ii) it can be directly converted into the more chemically stable compound xanthurenic acid (XA) by irreversible transamination. In rodents and humans, this latter function is provided by the same kynurenine aminotransferase (KAT) isozymes that are responsible for the pyridoxal 5Ј-phosphate (PLP)-dependent transformation of L-KYN into the neuroprotective and anticonvulsant NMDA receptor antagonist kynurenic acid (KA) (18)(19)(20).…”
mentioning
confidence: 99%